PKM Penulisan Karya Ilmiah Mahasiswa: Pengenalan Manajemen Mendeley serta Penulisan Title, Authorship, Abstract, Keyword, and References - Siti Ida Yanti; Rabya Mulyawati Ahmad; Ma’ruf Ishak Ola; Sayyidaturrofidah; Nurfatihati (LP3M IAIFA Kediri, 2025)
The Community Service Program (PKM) entitled “Scientific Writing Training for Students: Introduction to Mendeley Management and the Writing of Title, Authorship, Abstract, Keyword, and References” was conducted at Sekolah Tinggi Agama Islam (STAI) Kupang, East Nusa Tenggara, on August 15, 2025. The objectives of this program were: (1) to strengthen students’ competence in using Mendeley for reference and citation management according to academic standards; (2) to equip students with practical skills in developing effective titles, communicative abstracts, relevant keywords, and consistent ethical references, including a clear understanding of authorship; and (3) to foster a productive academic culture through the development of a sustainable tradition of scientific writing among students. A participatory-collaborative approach was employed to encourage active interaction between facilitators and students in every stage of the program—planning, implementation, and evaluation. The one-day training was organized into four main sessions: orientation, technical training, mentoring, and evaluation. Data were collected through interviews to assess improvements in participants’ understanding and skills. The results indicated a significant enhancement in students’ ability to manage references, structure academic papers, and apply academic writing ethics. Students also demonstrated increased awareness of plagiarism prevention and initiated peer mentoring activities to sustain the academic writing culture. This PKM successfully strengthened students’ digital literacy and academic integrity as a foundation for cultivating a strong scientific tradition in higher education.